“Exosomics”—A Review of Biophysics, Biology and Biochemistry of Exosomes With a Focus on Human Breast Milk - de la Torre Gomez, Carolina; Goreham, Renee V.; Bech Serra, Joan J.; Nann, Thomas; Kussmann, Martin (Frontiers in Genetics, 2018)
Exosomes are biomolecular nanostructures released from cells. They carry specific biomolecular information and are mainly researched for their exquisite properties as a biomarker source and delivery system. We introduce exosomes in the context of other extracellular vesicles, describe their biophysical isolation and characterisation and discuss their biochemical profiling. Motivated by our interest in early-life nutrition and health, and corresponding studies enrolling lactating mothers and their infants, we zoom into exosomes derived from human breast milk. We argue that these should be more extensively studied at proteomic and micronutrient profiling level, because breast milk exosomes provide a more specific window into breast milk quality from an immunological (proteomics) and nutritional (micronutrient) perspective. Such enhanced breast milk exosome profiling would thereby complement and enrich the more classical whole breast milk analysis and is expected to deliver more functional insights than the rather descriptive analysis of human milk, or larger fractions thereof, such as milk fat globule membrane. We substantiate our arguments by a bioinformatic analysis of two published proteomic data sets of human breast milk exosomes.